Ethical Dilemmas in Tax Planning for MSME Taxpayers in Facing Core Tax - Diki Suganda; Irwansyah; Zaki Fakhroni (Proceeding International Conference on Accounting and Finance, 2025)
This study examines the ethical dilemmas faced by Micro, Small, and Medium Enterprises (MSMEs) in tax planning ahead of the Core Tax Administration System (Core Tax) implementation. The study employs a qualitative case study approach on MSMEs in Samarinda, revealing a significant fear among business owners about their classification as Taxable Entrepreneurs (PKP), particularly when their annual revenues are close to or surpass IDR 4.8 billion. This fear prompts strategies like delaying revenue reporting, distributing revenue among family members, or omitting sales. Prospect Theory explains this behavior, showing MSME owners prioritize avoiding potential losses, such as losing customers from price hikes due to VAT, over the benefits of tax compliance. The real-time monitoring by Core Tax intensifies this dilemma, which is further complicated by limited resources and simple administrative practices that complicate adherence to stricter tax regulations. The study also reveals dissatisfaction with tax policies, particularly the PKP threshold, which is perceived as unfair and disconnected from business realities. The research emphasizes the need for fairer tax policies, enhanced support for MSMEs, and greater government transparency to build trust and improve compliance.